EVALUASI USAHA PENGOLAHAN SUWIR-SUWIR IKAN CAKALANG DI DESA NAMLEA - Sariani Sariani; Stevanus Marelly Siahainenia; Eygner Gerald Talakua (Universitas Pattimura, 2017)
This study aims to examine the business benefits, added value, and business risks of skipjack processing (suwir-suwir) at POKLAHSAR Huhate in Namlea Village as a first step in evaluating newly established businesses in 2011. Primary data were collected from research informants (owner company and labor) through observation and direct interview with questionnaire. Data analysis was done by qualitative descriptive analysis method, including business profit analysis method, value added analysis method, and business risk analysis method. The results showed that: 1). The business profit is Rp 1.205.945,-/production; 2). Added value of Rp 40.654-,/kg, or 65.05% against the sale value of skipjack suwir by Rp 62.500,-; and 3). The risk of suwir-suwir skipjack business of POKLAHSAR Huhate in Namlea Village has no chance of losing any production process or this business will always experience profit because the lower profit margin is positive at Rp 98.,971,21.